2015
DOI: 10.1002/ange.201502290
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Synthesis of the Potent HIV Inhibitor BMS‐986001 by Non‐Enzymatic Dynamic Kinetic Asymmetric Transformation (DYKAT)

Abstract: Described herein is the synthesis of BMS‐986001 by employing two novel organocatalytic transformations: 1) a highly selective pyranose to furanose ring tautomerization to access an advanced intermediate, and 2) an unprecedented small‐molecule‐mediated dynamic kinetic resolution to access a variety of enantiopure pyranones, one of which served as a versatile building block for the multigram, stereoselective, and chromatography‐free synthesis of BMS‐986001. The synthesis required five chemical transformations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The intended use of the labeled analog, the known metabolism, the length of the synthesis and the cost of the labeled starting materials all have to be considered when developing a labeling strategy. Looking at the synthetic route being used to produce unlabeled 1, [7][8][9] it was clear the shortest and least expensive route to carbon-14 labeled 1 would be to incorporate the label into the thymine base. A metabolism study using unlabeled 1 suggested the nucleoside base would not be the best site for the carbon-14 label from a safety standpoint.…”
Section: Results Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The intended use of the labeled analog, the known metabolism, the length of the synthesis and the cost of the labeled starting materials all have to be considered when developing a labeling strategy. Looking at the synthetic route being used to produce unlabeled 1, [7][8][9] it was clear the shortest and least expensive route to carbon-14 labeled 1 would be to incorporate the label into the thymine base. A metabolism study using unlabeled 1 suggested the nucleoside base would not be the best site for the carbon-14 label from a safety standpoint.…”
Section: Results Discussionmentioning
confidence: 99%
“…The reported procedure to install the acetylene in the sugar used 2.5 eq of trimethylsilylacetylene. 9 This procedure as described would be unacceptable for the synthesis of labeled material since using such a large excess of the labeled starting material would give the desired product in an unsustainably low radiochemical yield. A series of probe reactions with varying amounts of unlabeled trimethylsilylacetylene and ketone 4 were conducted as shown in Table 1 in an attempt to optimize the yield of 5 in the reaction in Scheme 1.…”
Section: Results Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[28] Researchers at Bristol-Myers Squibb reported ad ynamic kinetic enantioselective acylation (DKEA) of several lactols with either two hydrogen or two methyl substituents on the 5-position to the corresponding esters with up to 88 % ee (Scheme10). [29] Commercially available( À)-levamisole was used as the catalystf or this DKEA reaction. An elegants ynthesis of anti-HIV drug BMS-986001w as accomplished in five steps by using this method.…”
Section: Formation Of Dihydropyrans By Achmatowicz Rearrangementmentioning
confidence: 99%